2000
DOI: 10.1021/jm990075h
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on Nociceptin-Related Peptides:  Discovery of a New Chemical Template with Antagonist Activity on the Nociceptin Receptor

Abstract: Three series of nociceptin (NC)-related peptides were synthesized and their abilities (i) to bind to the NC sites expressed in mouse forebrain membranes, (ii) to inhibit the electrically evoked contraction of the mouse vas deferens, and (iii) to inhibit forskolin-stimulated cAMP accumulation in Chinese hamster ovary cells expressing the human recombinant NC receptor (CHONCR) were investigated. The compounds of the first series (a series) have an ordinary Xaa1-Gly2 bond, those of the second series (b series) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
83
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 60 publications
2
83
0
Order By: Relevance
“…[Nphe 1 ]NC(1-13)NH 2 inhibits the binding of a tritiated nociceptin analogue to mouse brain membranes with a K i = 100 nM [51]. Despite this low affinity, [Nphe 1 ]NC(1-13)NH 2 was able to antagonize forskolinstimulated cAMP accumulation in CHO cells transfected with human ORL 1 with a pK b of 6.1 and to antagonize the nociceptin-induced contraction in electrically stimulated mouse vas deferens with a pK b of 6.4 [51].…”
Section: Orl 1 Receptor Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…[Nphe 1 ]NC(1-13)NH 2 inhibits the binding of a tritiated nociceptin analogue to mouse brain membranes with a K i = 100 nM [51]. Despite this low affinity, [Nphe 1 ]NC(1-13)NH 2 was able to antagonize forskolinstimulated cAMP accumulation in CHO cells transfected with human ORL 1 with a pK b of 6.1 and to antagonize the nociceptin-induced contraction in electrically stimulated mouse vas deferens with a pK b of 6.4 [51].…”
Section: Orl 1 Receptor Ligandsmentioning
confidence: 99%
“…[Nphe 1 ]NC(1-13)NH 2 inhibits the binding of a tritiated nociceptin analogue to mouse brain membranes with a K i = 100 nM [51]. Despite this low affinity, [Nphe 1 ]NC(1-13)NH 2 was able to antagonize forskolinstimulated cAMP accumulation in CHO cells transfected with human ORL 1 with a pK b of 6.1 and to antagonize the nociceptin-induced contraction in electrically stimulated mouse vas deferens with a pK b of 6.4 [51]. Most promisingly, the ligand did not show any residual agonist activity and was able to prevent the effects of nociceptin in the mouse tail withdrawal assay and to potentiate morphineinduced analgesia [52].…”
Section: Orl 1 Receptor Ligandsmentioning
confidence: 99%
“…Details about these three classes of NOP ligands can be found in recent review articles such as [53] and [3]. Our research group has substantially contributed to the identification of N/OFQ related NOP ligands by performing a series of structure activity studies which allow the identification of the following useful chemical modifications: C-terminus amidation that increases agonist potency and reduces susceptibility to peptidases [23], reduction of the first peptide bond of N/OFQ which reduces ligand efficacy [8], shift of the Phe 1 side chain to the nitrogen atom that eliminates efficacy [25], and substitutions on the Phe 4 side chain (e.g. (pF)Phe 4 ) that increase peptide potency [24].…”
Section: Introductionmentioning
confidence: 99%
“…Identification of such new molecules (at least of peptide nature) should be facilitated by the knowledge of the amino acid residues of the NC sequence that are critical for receptor occupation and activation. Over the last 5 years, several structure-activity relationship studies have been performed on NC (Dooley and Houghten, 1996;Reinscheid et al, 1996;Butour et al, 1997;Guerrini et al, 1997;Calo' et al, 1998a;Guerrini et al, 2000a). These studies suggested that Phe 1 and Phe 4 represent the critical residues of the message domain of NC (Phe 1 -Gly 2 -Gly 3 -Phe 4 ), which should be involved in receptor binding and activation, whereas the positively charged residues that are present in the address domain of the molecule (Arg 8,12 , Lys 9,13 ) appear to be crucial for receptor occupation.…”
mentioning
confidence: 99%
“…In Guerrini et al, 2000a), J-113397 (Kawamoto et al, 1999), and the nonselective opioid receptor antagonist naloxone. The effects of [Arg 14 ,Lys 15 ]NC were also evaluated in vivo, in the locomotor activity and in the tail-withdrawal assays after i.c.v.…”
mentioning
confidence: 99%